If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=(-13)-3x
We simplify the equation to the form, which is simple to understand
-2=(-13)-3x
Remove unnecessary parentheses
-2=-13-3x
We move all terms containing x to the left and all other terms to the right.
+3x=-13+2
We simplify left and right side of the equation.
+3x=-11
We divide both sides of the equation by 03 to get x.
x=-3.6666666666667
| 2b+3l=42.50 | | 10+11x=16x | | 17.77=3g+3.91 | | -17=p-8 | | -5x-10=9x+15 | | 9x+18=-72 | | 11=7x+2-4x | | 7-9x-3=-80+5x-14 | | 6w^2-11w-21=0 | | 3x+1.1=9.2 | | 4.905*x^2-20x=0 | | 5x-2x-2=13 | | -126=9b | | 2x+15=3+7x-8 | | 2x+3-4=17 | | 75=1ry | | 2-5x-9=18 | | sqrt(10-x)=x-4 | | 7-3.5=38 | | -5.1=2.9-4y | | 4z+2=z-4 | | 5+2(x+9)=-17 | | 20x-4.905x^2=0 | | 4(x-7)=64 | | -1=-17+p | | -2(2-4x)+2x-6=3x-1 | | 3800=600 | | x^2-2x-210=0 | | sqrt(2x+1)=6 | | 46=2(9+w) | | -6+8r=-(6-8r) | | 7x-(2x-11)=41 |